Cover Image. Issue 3 (5th August 2021) - Hoffmann, Malte; Abaci Turk, Esra; Gagoski, Borjan; Morgan, Leah; Wighton, Paul; Tisdall, Matthew Dylan; Reuter, Martin; Adalsteinsson, Elfar; Grant, Patricia Ellen; Wald, Lawrence L.; van der Kouwe, André J. W.
Abstract : The cover image is based on the Original Article Rapid head‐pose detection for automated slice prescription of fetal‐brain by Malte Hoffmann et al., https://doi.org/10.1002/ima.22563 . Abstract : The cover image is based on the Original Article Rapid head‐pose detection for automated slice prescription of fetal‐brain by Malte Hoffmann et al., https://doi.org/10.1002/ima.22563 .